Integrally formed ceramic matrix composite honeycomb and its preparation method and application

Through an integrated molding process, including setting, curing and splicing of seam fiber cloth, and depositing boron nitride interface layer and ceramic matrix on it, the problems of low bond strength and low compressive strength in ceramic matrix composite honeycombs are solved, and efficient honeycomb preparation of ceramic matrix composite honeycombs is achieved, with excellent high temperature resistance and mechanical properties.

CN117024169BActive Publication Date: 2025-05-30NORTHWESTERN POLYTECHNICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310882752.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-03-17
Filing Date
2023-07-18
Publication Date
2025-05-30
Estimated Expiration
2043-07-18

AI Technical Summary

Technical Problem

The problem of low internal bonding strength at the connections of existing ceramic matrix composite materials and low overall compressive strength.

Method used

By obtaining corrugated fiber cloth, shaped, cured and spliced ​​and sewn, forming a honeycomb fiber preform, and then using chemical vapor permeation method to deposit boron nitride interface layer and ceramic matrix on the fiber preform, realizing integrated molding to prepare honeycombs of ceramic matrix composite material.

Benefits of technology

The bonding strength and overall compressive strength at the internal connections of the honeycomb are improved, and the high temperature resistance of the material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117024169B_ABST
    Figure CN117024169B_ABST
Patent Text Reader

Abstract

The present invention discloses an integrally formed ceramic matrix composite honeycomb, its preparation method and application, relating to the technical field of ceramic matrix composites. It includes obtaining corrugated fiber cloth; obtaining a corrugated fiber preform; obtaining a honeycomb-shaped fiber preform; depositing a boron nitride interface layer on the honeycomb-shaped fiber preform; and depositing a ceramic matrix on the surface of the boron nitride interface layer to obtain a ceramic matrix composite honeycomb. The ceramic matrix composite honeycomb prepared by the present invention improves the bonding strength at the joints inside the honeycomb through an integrally formed technology, and is a lightweight composite material with high temperature resistance and high strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic matrix composites, and particularly to an integrally formed ceramic matrix composite honeycomb and its preparation method and application. Background Art

[0002] As an important lightweight structure, honeycomb structure composites have many advantages compared with traditional materials, such as low mass, high specific strength, good heat insulation performance, and good designability. They are widely used in civil fields such as aviation, aerospace, ships, and automobiles. In the aerospace field, honeycomb structures are mostly used in the wings, tails, etc. of aircraft. However, for hypersonic aircraft, the too-fast flight speed causes the temperature at the wings and tails to be too high, and common honeycomb materials, such as aramid paper honeycombs, cannot withstand such high temperatures. Therefore, researching high-temperature resistant honeycomb materials has very important value.

[0003] Ceramic matrix composites have the characteristics of low mass, high temperature resistance, and excellent high-temperature mechanical properties. Preparing a ceramic matrix composite honeycomb with a ceramic matrix composite as the skeleton can effectively increase the service temperature of the honeycomb, thereby reducing the weight of the hypersonic aircraft and improving its thermal protection performance at the same time.

[0004] When preparing a ceramic matrix composite honeycomb by the existing method, generally, a corrugated fiber preform or composite material is first prepared and then connected together by an adhesive to obtain a ceramic matrix composite honeycomb. However, the bonding method will result in a low bonding strength at the joints inside the honeycomb, which is prone to separation under external forces, and the overall compressive strength of the honeycomb is not high. Summary of the Invention

[0005] In order to solve the deficiencies in the prior art, the present invention provides an integrally formed ceramic matrix composite honeycomb and its preparation method and application. It mainly solves the problems of low internal bonding strength at the joints and low overall compressive strength in the existing ceramic matrix composite honeycombs.

[0006] The first object of the present invention is to provide a preparation method for an integrally formed ceramic matrix composite honeycomb, including the following steps:

[0007] Obtain corrugated fiber cloth;

[0008] Immerse the corrugated fiber cloth in a ceramic precursor solution, and after curing and demolding, obtain a corrugated fiber preform;

[0009] Splice and stitch the corrugated fiber preforms to obtain a honeycomb-shaped fiber preform;

[0010] Place the honeycomb-shaped fiber preform in a deposition furnace, introduce argon, hydrogen, boron trichloride, and ammonia gas, and deposit a boron nitride interface layer on the honeycomb-shaped fiber preform;

[0011] Place the honeycomb fiber preform with the interface layer deposited in a deposition furnace, introduce argon, hydrogen, and the gas corresponding to different matrices, and deposit a ceramic matrix on the surface of the boron nitride interface layer to obtain a honeycomb of ceramic matrix composite material.

[0012] Preferably, the corrugated fiber cloth is obtained by shaping the fiber cloth into a corrugated shape through a mold.

[0013] Preferably, the fiber cloth includes carbon fiber cloth, silicon carbide fiber cloth, silicon nitride fiber cloth, or alumina fiber cloth.

[0014] Preferably, the solvent in the ceramic precursor solution is one of xylene, cyclohexane, and tetrahydrofuran, and the ceramic precursor is one of polysilazane (PSN), polyborosilazane (PBSN), polycarbosilane (PCS), and polysiloxane (PSO); wherein, the volume ratio of the solvent to the ceramic precursor is 1:3 - 6.

[0015] Preferably, when depositing the boron nitride interface layer, the temperature in the deposition furnace is 700 - 900 °C, the pressure is 2 - 5 KPa, introduce argon, hydrogen, boron trichloride, and ammonia, where argon is used as a dilution gas, hydrogen is used as a carrier gas, boron trichloride is used as a boron source, and ammonia is used as a nitrogen source. Through the reaction of boron trichloride and ammonia, a boron nitride interface layer is formed on the surface of the honeycomb fiber preform.

[0016] More preferably, when depositing the boron nitride interface layer, the deposition time is 30 - 70 h, and the thickness of the boron nitride interface layer is 300 - 700 nm.

[0017] Preferably, when depositing the ceramic matrix on the surface of the boron nitride interface layer, it includes:

[0018] The pressure in the deposition furnace is 2 - 6 KPa, the temperature is 800 - 1000 °C, introduce argon, hydrogen, and reaction gas, and deposit the ceramic matrix on the surface of the boron nitride interface layer; the deposition time is 90 - 130 h.

[0019] More preferably, when the ceramic matrix is silicon nitride, the reaction gas introduced is silicon tetrachloride and ammonia; when the ceramic matrix is silicon carbide, the reaction gas introduced is methyltrichlorosilane.

[0020] The second object of the present invention is to provide a honeycomb of ceramic matrix composite material with integrated molding.

[0021] The third object of the present invention is to provide an application of a honeycomb of ceramic matrix composite material with integrated molding in high-temperature and high-strength electromagnetic wave absorption materials.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] The present invention obtains a honeycomb-shaped fiber preform by shaping, curing, and splicing and sewing fiber cloth, and then uses a chemical vapor infiltration method to integrally form a ceramic matrix composite honeycomb. The internal joints of the sewn honeycomb-shaped fiber preform are tightly combined, which is beneficial to the CVI deposition interface and the matrix. After passing through the CVI deposition interface and the matrix, the fiber preforms on both sides of the joint together form a composite material, and the joint is inside the composite material, forming a chemical bond. Compared with the physical bond of forming a honeycomb by connecting corrugated composite materials together with an adhesive, the ceramic matrix composite honeycomb prepared by the integral forming method of the present invention not only has good heat resistance, but also has high internal bonding strength and relatively high overall compressive strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a process flow chart for preparing a ceramic matrix composite honeycomb.

[0025] Figure 2 It is a schematic diagram of a mold.

[0026] Figure 3 It is a photo of a corrugated fiber preform.

[0027] Figure 4 It is a photo of a honeycomb-shaped fiber preform.

[0028] Figure 5 It is the SiC / Si provided in Example 1 3 N 4 It is a test chart of the high-temperature wave absorption performance of the ceramic matrix composite honeycomb at 1000 °C. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0029] The present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments, so that those skilled in the art can better understand the present invention and be able to implement it, but the embodiments cited do not limit the present invention.

[0030] The present invention provides a method for preparing an integrally formed ceramic matrix composite honeycomb, including the following steps:

[0031] Obtain corrugated fiber cloth;

[0032] Immerse the corrugated fiber cloth in a ceramic precursor solution, cure it, and demold it to obtain a corrugated fiber preform;

[0033] Splice and sew the corrugated fiber preform to obtain a honeycomb-shaped fiber preform;

[0034] Place the honeycomb-shaped fiber preform in a deposition furnace, introduce argon, hydrogen, boron trichloride, and ammonia gas, and deposit a boron nitride interface layer on the honeycomb-shaped fiber preform;

[0035] Place the honeycomb fiber preform with the deposited interface layer in a deposition furnace, introduce argon, hydrogen, and the gas corresponding to different matrices, and deposit a ceramic matrix on the surface of the boron nitride interface layer to obtain a honeycomb of ceramic matrix composite material.

[0036] In the present invention, a honeycomb fiber preform is obtained by shaping, curing, and splicing and sewing a fiber cloth, and then a honeycomb of ceramic matrix composite material is integrally formed by a chemical vapor infiltration method. The prepared honeycomb of ceramic matrix composite material not only has good heat resistance but also has high internal bonding strength and relatively high overall compressive strength.

[0037] Among them, the corrugated fiber cloth is obtained by shaping the fiber cloth into a corrugated shape through a mold.

[0038] Specifically, shaping the fiber cloth into a corrugated shape includes:

[0039] Cut the fiber cloth according to the size of the mold and stack it layer by layer. The number of stacked layers of the fiber cloth depends on the wall thickness of the honeycomb wall, and then use the mold to shape the fiber cloth into a corrugated shape.

[0040] The fiber cloth includes carbon fiber cloth, silicon carbide fiber cloth, silicon nitride fiber cloth, or alumina fiber cloth.

[0041] According to the present invention, the solvent in the ceramic precursor solution is one of xylene, cyclohexane, and tetrahydrofuran, and the ceramic precursor is one of polysilazane (PSN), polyborosilazane (PBSN), polycarbosilane (PCS), and polysiloxane (PSO); wherein, the volume ratio of the solvent to the ceramic precursor is 1:3 - 6.

[0042] Among them, when depositing the boron nitride interface layer, the temperature in the deposition furnace is 700 - 900 °C, the pressure is 2 - 5 KPa, and argon, hydrogen, boron trichloride, and ammonia are introduced. Argon is used as a dilution gas, hydrogen is used as a carrier gas, boron trichloride is used as a boron source, and ammonia is used as a nitrogen source. Through the reaction of boron trichloride and ammonia, a boron nitride interface layer is formed on the surface of the honeycomb fiber preform.

[0043] When depositing the boron nitride interface layer, the deposition time is 30 - 70 h, and the thickness of the boron nitride interface layer is 300 - 700 nm.

[0044] Among them, when depositing the ceramic matrix on the surface of the boron nitride interface layer, it includes:

[0045] The pressure in the deposition furnace is 2 - 6 KPa, the temperature is 800 - 1000 °C, and argon, hydrogen, and reaction gas are introduced to deposit the ceramic matrix on the surface of the boron nitride interface layer; the deposition time is 90 - 130 h.

[0046] When the ceramic matrix is silicon nitride, the reaction gases introduced are silicon tetrachloride and ammonia; when the ceramic matrix is silicon carbide, the reaction gas introduced is methyltrichlorosilane.

[0047] The present invention provides a ceramic matrix composite honeycomb with integral molding.

[0048] The present invention provides an application of the ceramic matrix composite honeycomb with integral molding in high-temperature and high-strength electromagnetic wave absorption materials.

[0049] In the present invention, by shaping, curing and splicing and sewing the fiber cloth, a honeycomb-shaped fiber preform is obtained, and then by using the chemical vapor infiltration method, a ceramic matrix composite honeycomb is integrally molded. The prepared ceramic matrix composite honeycomb not only has good heat resistance, but also has high internal bonding strength and relatively high overall compressive strength.

[0050] In one embodiment, a preparation method of the ceramic matrix composite honeycomb with integral molding is as Figure 1 shown, and includes the following steps:

[0051] Step 1, cut the fiber cloth according to the size of the mold ( Figure 2 ), stack it layer by layer, the stacking layers of the fiber cloth depend on the wall thickness of the honeycomb wall, and then use the mold to shape the fiber cloth into a corrugated shape to obtain a corrugated fiber cloth;

[0052] Step 2, immerse the fiber cloth in step 1 in a ceramic precursor solution, cure and demold to obtain a corrugated fiber preform;

[0053] Step 3, splice and sew the corrugated fiber preform in step 2 with fibers to obtain a honeycomb-shaped fiber preform;

[0054] Step 4, put the honeycomb-shaped fiber preform in step 3 into a deposition furnace, introduce argon, hydrogen, boron trichloride and ammonia, and deposit a boron nitride interface layer under high temperature and high pressure;

[0055] Step 5, put the fiber preform with the interface layer deposited in step 4 into a deposition furnace, introduce argon, hydrogen and the gas corresponding to different matrices, and deposit a ceramic matrix on the surface of the boron nitride interface layer to obtain a ceramic matrix composite honeycomb.

[0056] In the said step 1, the fiber cloth is one of carbon fiber cloth, silicon carbide fiber cloth, silicon nitride fiber cloth, alumina fiber cloth, the width of the fiber cloth is 5 - 20 mm, the length is 280 - 350 mm, and the stacking layers are 4 - 12 layers.

[0057] In step 2, the solvent in the ceramic precursor solution is one of xylene, cyclohexane, and tetrahydrofuran, and the ceramic precursor is one of polysilazane (PSN), polyborosilazane (PBSN), polycarbosilane (PCS), and polysiloxane (PSO). The volume ratio of the solvent to the ceramic precursor is 1:3 - 6, the curing temperature is 150 - 180°C, and the curing time is 3 - 6 h.

[0058] In step 3, the fiber used for stitching is one of glass fiber and carbon fiber.

[0059] In step 4, the temperature in the deposition furnace is 700 - 900°C, the pressure is 2 - 5 KPa, and argon, hydrogen, boron trichloride, and ammonia are introduced. Among them, argon is used as the dilution gas, hydrogen is used as the carrier gas, boron trichloride is used as the boron source, and ammonia is used as the nitrogen source. The flow rate of argon is 4 - 7 L / min, the flow rate of hydrogen is 8 - 11 L / min, the flow rate of boron trichloride is 3 - 7 L / min, and the flow rate of ammonia is 4 - 8 L / min. Under high temperature and high pressure, boron trichloride and ammonia react to form a boron nitride interface layer on the surface of the honeycomb fiber preform. The deposition time is 30 - 70 h, and the thickness of the boron nitride interface layer is 300 - 700 nm.

[0060] In step 5, the temperature in the deposition furnace is 800 - 1000°C, the pressure is 2 - 6 KPa, and argon, hydrogen, and reaction gas are introduced. A ceramic matrix is deposited on the surface of the boron nitride interface layer. Depending on the matrix, the reaction gas is silicon tetrachloride and ammonia (when the matrix is silicon nitride) or methyltrichlorosilane (when the matrix is silicon carbide). The flow rate of argon is 4 - 7 L / min, the flow rate of hydrogen is 8 - 11 L / min, the flow rate of silicon tetrachloride is 3 - 6 L / min, the flow rate of ammonia is 4 - 6 L / min, and the flow rate of methyltrichlorosilane is 4 - 9 L / min. The deposition time is 90 - 130 h.

[0061] Example 1

[0062] Step 1: Cut the silicon carbide fiber cloth into strips with a width of 5 mm and a length of 280 mm, and stack four layers in the mold to obtain a corrugated fiber cloth.

[0063] Step 2: Immerse the fiber cloth in step 1 in the ceramic precursor solution. The ceramic precursor solution is made of xylene and polyborosilazane in a volume ratio of 1:5, and then cured at 170°C for 3 h. After cooling, demold to obtain a corrugated fiber preform, as Figure 3 shown;

[0064] Step 3: Use glass fiber to splice and stitch the corrugated fiber preform in step 2 to obtain a honeycomb fiber preform, as Figure 4 shown;

[0065] Step 4: Place the honeycomb fiber preform obtained in Step 3 into a deposition furnace. Introduce argon, hydrogen, boron trichloride, and ammonia. The temperature is 700 °C, the pressure is 5 KPa, the argon flow rate is 5 L / min, the hydrogen flow rate is 8 L / min, the boron trichloride flow rate is 4 L / min, and the ammonia flow rate is 7 L / min. React for 30 h to deposit a boron nitride interface layer on the surface of the fiber preform.

[0066] Step 5: Place the fiber preform with the deposited interface layer obtained in Step 4 into a deposition furnace. Introduce argon, hydrogen, silicon tetrachloride, and ammonia. The temperature is 900 °C, the pressure is 4 KPa, the argon flow rate is 5 L / min, the hydrogen flow rate is 9 L / min, the silicon tetrachloride flow rate is 4 L / min, and the ammonia flow rate is 5 L / min. React for 90 h to deposit a silicon nitride matrix on the surface of the boron nitride interface layer, obtaining a SiC / Si 3 N 4 honeycomb ceramic matrix composite.

[0067] The obtained SiC / Si 3 N 4 honeycomb composite is oxidized in air at 1000 °C for 2 h. The structure does not show deformation or cracking, and the compressive strength can reach 15 MPa, indicating that the SiC / Si 3 N 4 honeycomb composite has excellent high-temperature resistance and mechanical properties.

[0068] The obtained SiC / Si 3 N 4 honeycomb composite absorber is tested for its high-temperature microwave absorption performance at 1000 °C. Its high-temperature microwave absorption performance is as Figure 5 shown. The SiC / Si 3 N 4 honeycomb composite has an effective microwave absorption bandwidth (less than -10 dB) of up to 12.7 GHz in the 2 - 18 GHz frequency band range and can achieve a full frequency less than -7 dB in the 2 - 18 GHz range, showing excellent high-temperature broadband microwave absorption performance.

[0069] Example 2

[0070] Step 1: Cut the silicon carbide fiber cloth into strips with a width of 10 mm and a length of 300 mm. Stack six layers in a mold to obtain a corrugated fiber cloth.

[0071] Step 2: Immerse the fiber cloth obtained in Step 1 in a ceramic precursor solution. The ceramic precursor solution is made of cyclohexane and polycarbosilane in a volume ratio of 1:3. Then cure at 150 °C for 5 h, and demold after cooling to obtain a corrugated fiber preform.

[0072] Step 3: Use carbon fiber to splice and stitch the corrugated fiber preform in Step 2 to obtain a honeycomb fiber preform;

[0073] Step 4: Place the honeycomb fiber preform in Step 3 into a deposition furnace, and introduce argon, hydrogen, boron trichloride, and ammonia. The temperature is 800 °C, the pressure is 4 KPa, the argon flow rate is 6 L / min, the hydrogen flow rate is 10 L / min, the boron trichloride flow rate is 5 L / min, and the ammonia flow rate is 5 L / min. React for 50 h to deposit a boron nitride interface layer on the surface of the fiber preform;

[0074] Step 5: Place the fiber preform with the deposited interface layer in Step 4 into a deposition furnace, and introduce argon, hydrogen, and methyltrichlorosilane. The temperature is 800 °C, the pressure is 5 KPa, the argon flow rate is 7 L / min, the hydrogen flow rate is 10 L / min, and the methyltrichlorosilane flow rate is 5 L / min. React for 120 h to deposit a silicon carbide matrix on the surface of the boron nitride interface layer to obtain a SiC / SiC ceramic matrix composite honeycomb.

[0075] The obtained SiC / SiC composite honeycomb is oxidized in an air atmosphere at 1200 °C for 4 h, and no deformation or cracking occurs in the structure, and the compressive strength can reach 18 MPa, indicating that the SiC / SiC composite honeycomb has excellent high-temperature resistance and mechanical properties.

[0076] The obtained SiC / SiC composite wave-absorbing honeycomb is tested for high-temperature wave-absorbing performance at 1000 °C, and the effective wave-absorbing bandwidth (less than -10 dB) can reach 9.2 GHz in the frequency range of 2 - 18 GHz, and the full frequency can be less than -5 dB in the range of 2 - 18 GHz.

[0077] Example 3

[0078] Step 1: Cut the silicon nitride fiber cloth into strips with a width of 20 mm and a length of 330 mm, and stack ten layers in a mold to obtain a corrugated fiber cloth;

[0079] Step 2: Immerse the fiber cloth in Step 1 in a ceramic precursor solution, which is made of xylene and polyborosilazane in a volume ratio of 1:4, and then cure at 160 °C for 4 h. After cooling, demold to obtain a corrugated fiber preform;

[0080] Step 3: Use glass fiber to splice and stitch the corrugated fiber preform in Step 2 to obtain a honeycomb fiber preform;

[0081] Step 4: Place the honeycomb fiber preform in Step 3 into a deposition furnace, and introduce argon, hydrogen, boron trichloride, and ammonia. The temperature is 900 °C, the pressure is 3 KPa, the argon flow rate is 7 L / min, the hydrogen flow rate is 9 L / min, the boron trichloride flow rate is 7 L / min, and the ammonia flow rate is 6 L / min. React for 60 h to deposit a boron nitride interface layer on the surface of the fiber preform.

[0082] Step 5: Place the fiber preform with the deposited interface layer in Step 4 into a deposition furnace, and introduce argon, hydrogen, and methyltrichlorosilane. The temperature is 1000 °C, the pressure is 3 KPa, the argon flow rate is 6 L / min, the hydrogen flow rate is 8 L / min, and the methyltrichlorosilane flow rate is 8 L / min. React for 100 h to deposit a silicon carbide matrix on the surface of the boron nitride interface layer to obtain a Si 3 N 4 / SiC ceramic matrix composite honeycomb.

[0083] The obtained Si 3 N 4 / SiC composite honeycomb is oxidized in air at 1000 °C for 3 h. The structure does not show deformation or cracking, and the compressive strength can reach 12 MPa, indicating that the Si 3 N 4 / SiC composite honeycomb has excellent high-temperature resistance and mechanical properties.

[0084] The obtained Si 3 N 4 / SiC composite absorbing honeycomb is tested for high-temperature absorbing performance at 1000 °C. The effective absorbing bandwidth (less than -10 dB) can reach 11.5 GHz in the frequency range of 2 - 18 GHz, and the full frequency can be less than -6 dB in the range of 2 - 18 GHz.

[0085] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. A preparation method of an integrally formed ceramic matrix composite honeycomb, characterized in that, it includes the following steps: Obtain corrugated fiber cloth; Immerse the corrugated fiber cloth in a ceramic precursor solution, cure and demold to obtain a corrugated fiber preform; Splice and stitch the corrugated fiber preform to obtain a honeycomb fiber preform; Place the honeycomb fiber preform in a deposition furnace, introduce argon, hydrogen, boron trichloride and ammonia gas, and deposit a boron nitride interface layer on the honeycomb fiber preform; Place the honeycomb fiber preform with the deposited interface layer in a deposition furnace, introduce argon, hydrogen and the gas corresponding to different matrices, and deposit a ceramic matrix on the surface of the boron nitride interface layer to obtain a ceramic matrix composite honeycomb; The corrugated fiber cloth is obtained by shaping the fiber cloth into a corrugated shape through a mold; The fiber cloth includes carbon fiber cloth, silicon carbide fiber cloth, silicon nitride fiber cloth or alumina fiber cloth; In the ceramic precursor solution, the solvent is one of xylene, cyclohexane, and tetrahydrofuran, and the ceramic precursor is one of polysilazane, polyborosilazane, polycarbosilane, and polysiloxane; wherein, the volume ratio of the solvent to the ceramic precursor is 1:3 - 6; When depositing the boron nitride interface layer, the temperature in the deposition furnace is 700 - 900 °C, the pressure is 2 - 5 KPa, introduce argon, hydrogen, boron trichloride and ammonia gas, where argon is used as a dilution gas, hydrogen is used as a carrier gas, boron trichloride is used as a boron source, and ammonia gas is used as a nitrogen source. Through the reaction of boron trichloride and ammonia gas, a boron nitride interface layer is formed on the surface of the honeycomb fiber preform; When depositing the boron nitride interface layer, the deposition time is 30 - 70 h, and the thickness of the boron nitride interface layer is 300 - 700 nm; When depositing the ceramic matrix on the surface of the boron nitride interface layer, it includes: The pressure in the deposition furnace is 2 - 6 KPa, the temperature is 800 - 1000 °C, introduce argon, hydrogen and reaction gas, and deposit a ceramic matrix on the surface of the boron nitride interface layer; the deposition time is 90 - 130 h.

2. The preparation method of the integrally formed ceramic matrix composite honeycomb according to claim 1, characterized in that, when the ceramic matrix is silicon nitride, the reaction gas introduced is silicon tetrachloride and ammonia gas; when the ceramic matrix is silicon carbide, the reaction gas introduced is methyltrichlorosilane.

3. An integrally formed ceramic matrix composite honeycomb prepared by the method according to claim 1 or 2.

4. An application of the integrally formed ceramic matrix composite honeycomb according to claim 3 in a high-temperature and high-strength electromagnetic wave absorption material.

Citation Information

Patent Citations

  • Carbon honeycomb and preparation method thereof

    CN111647252A

  • Preparation method of ceramic-based composite material wave-absorbing honeycomb

    CN115745647A